Effect of Mistuning on the Detection of a Tone Masked by a Harmonic Tone Complex - Klein-Hennig, Martin; Dietz, Mathias; Klinge-Strahl, Astrid; Klump, Georg; Hohmann, Volker (PLOS ONE, 2012)
The human auditory system is sensitive in detecting “mistuned” components in a harmonic complex, which do not match the frequency pattern defined by the fundamental frequency of the complex. Depending on the frequency configuration, the mistuned component may be perceptually segregated from the complex and may be heard as a separate tone. In the context of a masking experiment, mistuning a single component decreases its masked threshold. In this study we propose to quantify the ability to detect a single component for fixed amounts of mistuning by adaptively varying its level. This method produces masking release by mistuning that can be compared to other masking release effects. Detection thresholds were obtained for various frequency configurations where the target component was resolved or unresolved in the auditory system. The results from 6 normal-hearing listeners show a significant decrease of masked thresholds between harmonic and mistuned conditions in all configurations and provide evidence for the employment of different detection strategies for resolved and unresolved components. The data suggest that across-frequency processing is involved in the release from masking. The results emphasize the ability of this method to assess integrative aspects of pitch and harmonicity perception.